Zur Bergbauernproblematik in Norwegen. Gezeigt an den Beispielen Fordal (Forbygda) und Budal in Sør-Trøndelag - Gläßer, Ewald; Hovstad, Håkon (ERDKUNDE, 1989)
This contribution addresses the problem of hill farming in Norway as it presents itself at Fordal and Budal in the province of Sør-Trøndelag, about one hour's motoring from Trondheim. Among other things the analysis considers the strategies of Norwegian agricultural policy. Furthermore, possibilities are explored of how far to keep at least parts of the area under investigation alive without subsidies of the present order of magnitude. The results of the investigation are mostly based on enquiries in the field and on specialized data from the agricultural authorities. Modern full-time farming is characterized by intensive dairy farming. Numbers in excess of twenty large animals on a cultivated area of not more than ten hectares can only be explained by massive production subsidies from the government. Besides this there are some specialized enterprises, such as the breeding of fur-bearing animals. At least in the hill farming areas investigated here, the agro-political interest ought to apply itself more to the combination of several branches of activity. The possibilities of forestry within agriculture, for instance, are by no means fully exploited at the present time. The overall picture also shows alternative occupations which are open to many parttime farmers, i.e. commuting farmers, in connection with activity in the primary sector. Enquiries revealed that younger members of families in particular show a keen interest in such combinations. This might be the most likely way of attaining the aim of Norwegian national planning to retain the existing settlement pattern as far as possible.